“Incidencia del desarrollo sostenible en la Implementación de proyectos Ecoturísticos; caso finca Agroturística los siete chorros; Cantón Píllaro” - Sánchez Guanopatín, Mercedes Elizabeth (2023)
The objective of this research work was to determine the incidence of sustainable development in the implementation of Ecotourism projects; Case: Agrotourism Farm "Los Siete Chorros"; Píllaro canton through environmental management and control in its different operations, to reduce the environmental impacts related to its operation. The methodological modality is mixed, while the type of research corresponds to field, descriptive and bibliographical; For the collection of information, an interview was designed and applied to the owner of the farm and a survey was designed for 211 visitors in order to collect information that supports their perception regarding sustainable development in ecotourism projects, likewise the check list was applied. of the ISO 14001:2015 standard to verify compliance with the requirements by the company, obtaining a very low compliance corresponding to 18%; On the other hand, as a result of the information collection, it was possible to establish that through the reduction of environmental impacts, ecotourism linked to sustainable development can be leveraged, therefore, it was concluded that the implementation of an EMS based on the ISO45001 standard can help reduce, control or eliminate its environmental impacts, making it viable to design an implementation proposal for the agrotourism farm "Los Siete Chorros".